High Lycopene Tomato Breeding Through Diallel Crossing - Muh Farid Bdr; Muhammad Fuad Anshori; Gracia Emanuella; Nur Pratiwi; Irna Ermiyanti; Vivi Yovita; M. Musdalifa; N. Nasaruddin (Universitas Sembilanbelas November Kolaka, 2020)
Tomatoes are known as one of the natural source of antioxidant, which is a compound that can inhibit and reduce oxidative cell and biomolecule damages, such as lipid, protein, and DNA. Health benefits from lycopene made this compound a tomato breeding subject for increasing its nutrient content. Tomato breeding is an environment friendly and sustainable method in agriculture biofortification methods, hence making the efforts for increasing tomato lycopene content to be possible. The aim of this research was to produce tomato hybrid with high lycopene and yield. This research was conducted in Experimental Farm, Faculty of Agriculture, Hasanuddin Univerisy, Makassar throughout June-Septermber 2020. This research was done in full diallel analysis using Griffing 1 method. Hybrid characters are highly determined with the presence of maternal effect. Lycopene has no correlation with productionCharacters correlated with lycopene are plant height, number of leaves, number of fruits per bunch, fruit length and fruit diameter, whilst productivity is correlated with number of leaves, stem diameter, and fruit diameter. Hybrids that can be used in further selection are CM, MC, MBC and KBC